Pengaruh Pemberian Susu Bubuk Afkir dan Jamu Tradisional Ke Dalam Air Minum Terhadap Performan Ayam Broiler - Hidayati, Sari Gando; Deyana, Ilham Putra; Syafrizal, Syafrizal (Jurnal Embrio, 2024)
This study aims to determine the effect of giving rejected milk powder and giving herbal medicine on body weight gain, feed consumption, and feed conversion in broiler chickens. The research was conducted by experimental method using a completely randomized design with a factorial pattern, namely Factor A (Milk Powder Afkir) with 3 levels (A1 = 0 g, A2 = 2.5 g and A3 = 5 g) and Factor B (Jamu) with 3 levels ( B1 = 0%, B2 = 0.5%, B3 = 1%) with 2 repetitions. The results of this study showed that the interaction of giving rejected milk powder and herbal medicine had no significant effect (P>0.05) on feed consumption, body weight gain and ration conversion. However, numerically, it shows an increase in body weight gain and a decrease in consumption and feed conversion. The single factor of rejected milk powder had no significant effect (P>0.05) on feed consumption, significantly (P<0.05) on body weight gain and very significant effect (P<0.01) on ration conversion. The single factor of herbal medicine had no significant effect (P>0.05) on feed consumption, body weight gain and ration conversion.